Direct oxidation of bromo-derived Fischer–Borsche oxo-ring using molecular iodine with combined experimental and computational study. Issue 29 (18th July 2022) - Humne, Vivek T.; Ghom, Monica H.; Naykode, Mahavir S.; Dangat, Yuvraj; Vanka, Kumar; Lokhande, Pradeep
Abstract : A direct oxidation of the bromo-derived Fischer–Borsche oxo-ring leading to carbazolequinone using iodine has been reported. This method has been used for the synthesis of the murrayaquinone and its derivatives, with good to excellent yield. Abstract : A direct oxidation of the bromo-derived Fischer–Borsche oxo-ring leading to carbazolequinone has been developed by using molecular iodine. This unprecedented transformation has been used for the modular synthesis of the anti-cardiotonic agent murrayaquinone. Furthermore, the present method has been generalized to a broad range of functional groups, with good to excellent yield.